BENTUK PERTUNJUKAN MUSIK PANCARAGAMDALAM ARAK-ARAKAN PENGANTEN DI KECAMATAN PAUH KOTA PADANG - Nisa, Hafiza Nurul; Wimbrayadi (Universitas Negeri Padang, 2025)
This research aims to describe the form of the pancaragam music performance in the wedding procession in Pauh sub-district, Padang City. The type of research used is qualitative with a descriptive method. The instruments for this research are the research themselves, supported by additional instruments such as writing tools and a camera. Data is collected through literature studies, observation, interviews, and documentation. The steps for analysing the data are collecting data, identifying data, clarifying data, describing data, and concluding data. The results of the research show that the form of the Pancaragam music performance in Pauh sub-district is flexible and does not have a fixed song structure. The performance is adjusted to the rhythm of the procession, consisting of an introduction, main theme, and transitions of songs that change spontaneously according to the mood or requests of the audience. The music played is repetitive in nature, using main instruments such as saxophone, trumpet, trombone, baritone, and drums as the main accompaniment for the procession. The style of the music ensemble performance demonstrates a distinctive musical hybridity, which is the fusion of Minangkabau traditional music, popular music such as dangdut and modern pop, as well as Western music elements. This style is reflected in the techniques of playing instruments, improvisation during performances, and the interaction between players and the audience which creates a dynamic and festive atmosphere. The music ensemble not only serves as entertainment in traditional ceremonies but also acts as a symbolic medium to strengthen social relationships within the Pauh community, as well as reinforce local cultural identity amid the influences of global culture.